Feeding the World Sustainably: Reflections Issues, and Suggestions - Serageldin, Ismail (2011)
2nd Annual Malthus Lecture "Feeding the World Sustainably: Reflections, Issues, and Suggestions" given by Dr. Ismail Serageldin at IFPRI on 14 July 2011. Co-hosted by IFPRI and PRB (Population Reference Bureau). Sponsored by Montague Yudelman.